Answer:
Step-by-step explanation:
To start you need to find the factorials of 8, -14, and 3 + 9i.
The factorials of these numbers are:
8: x - 8 = 0
-14: x + 14 = 0
3 + 9i: x - 3 - 9i = 0 *
3 - 9i: x - 3 + 9i = 0 *
(If you look in the files it shows how I got these numbers)
Next, you need to multiply the factorials together.
(x - 3 - 9i)(x - 3 + 9i) = x^2 - 6x + 90
Take that and multiply by your next factorial:
(x + 14)(x^2 - 6x + 90) = x^3 + 8x^2 + 6x + 1260
Multiply that by your final factorial and you have you final answer!
(x - 8)(x^3 + 8x^2 + 6x + 1260) = x^4 + 58x^2 + 1212x - 10,080
I hoped this helped!
*When you have 3 + 9i or anything along the lines of that then you need to find the inverse of it. You simply you simply change the sign that goes before the i term. Change <em>3 </em><em>+</em><em> 9i</em> to <em>3 </em><em>- </em><em>9i </em>